1995
DOI: 10.1136/hrt.74.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular morphology and diastolic function in uraemia: echocardiographic evidence of a specific cardiomyopathy.

Abstract: Objective-To see whether cardiac morphological and functional abnormalities in uraemic patients are determined by high blood pressure or if they are an expression of a specific cardiomyopathy. Design-Cross sectional study. Setting-City general hospital in Italy. Haemodialysis for chronic renal failure still carries high mortality (10% per year). Cardiovascular events are the main cause of death (50-60% against 15% in control populations).' Accelerated coronary atherosclerosis, which has been claimed to be li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
3
14
1
Order By: Relevance
“…This hypothesis would need to be tested with adequate range designed study. Surprisingly, being consistent with Facchin et al (17), most of diastolic parameters were not related to blood pressure. Explanation can be an impact of many factors (except those mentioned in the upper part of discussion, age, heart rate, circulating volume and others) to evaluate diastolic parameters.…”
Section: Discussionsupporting
confidence: 91%
“…This hypothesis would need to be tested with adequate range designed study. Surprisingly, being consistent with Facchin et al (17), most of diastolic parameters were not related to blood pressure. Explanation can be an impact of many factors (except those mentioned in the upper part of discussion, age, heart rate, circulating volume and others) to evaluate diastolic parameters.…”
Section: Discussionsupporting
confidence: 91%
“…[26][27][28][29] However, others could not confirm these findings and indicated that abnormalities in diastolic filling may occur early and before LVH and systolic dysfunction. [4,7] We did not find a significant correlation between LVMI and the E/A ratio, which was consistent with some reports in literature.…”
Section: Discussionmentioning
confidence: 74%
“…This goes together with many previous studies [13][14][15][16]. Although it is well established that relaxation is impaired in the hypertrophied myocardium [25], in CRF diastolic function does not necessarily correlate with the degree of LVH [15,16].…”
Section: Discussionmentioning
confidence: 90%
“…Although many studies suggest that cardiac systolic [9][10][11][12][13] and diastolic [13][14][15][16] function may be impaired in patients with CRF, it is still highly controversial if correction of the secondary hyperparathyroidism associated with CRF can improve left ventricular (LV) function. Some authors have reported an improvement in LV systolic function after parathyroidectomy [12,17] or vitamin D therapy [18], while several others [18][19][20] have failed to demonstrate improvement after parathyroidectomy.…”
Section: Introductionmentioning
confidence: 99%